Challenges and Solutions of Sustainable Apparel Product Development: A Case Study of Eileen Fisher. (January 2013) - Curwen, Lisa G.; Park, Juyeon; Sarkar, Ajoy K.
The three-fold purpose of this study is to document current challenges the apparel industry experiences in developing sustainable apparel, discover product development strategies for fulfilling sustainable business goals, and determine the principles guiding successful interaction between designers and the upstream supply chain. This study adopted a case study method to identify and communicate practical challenges and solutions of Eileen Fisher, a women's apparel manufacturer. Data were collected from thirteen in-depth interviews conducted with members of the case company and its suppliers, with secondary data analysis from the case company's website and archival records. The study identified five challenges the case company encountered with respect to maintaining product value, quality, and aesthetics, meeting needs of suppliers, and coping with higher material and labor costs. Five solutions were put into place supporting sustainability objectives, and which highlight the practice of innovation in design, optimizing timing and resources, gathering and diffusing information, relationship management, and making trade-offs for cost and value. Five principles, which guided the design team and its interaction with upstream suppliers, were identified and modeled. The implication for other apparel companies in overcoming challenges of sustainable product development is that it begins with a clear mission, strong company mandate, and like-minded supply partners. The authors believe that, in beginning to fill an area of limited research, examination of the connections between design process and the supply chain is imperative for advancing sustainable practices in the apparel and textile industry.